Avaliação das propriedades mecânicas e da durabilidade do concreto com cinzas da termoelétrica do Pecém/CE - Silva, David Alison Araújo (2017)
The mineral coal of combustion ashes (MCCA) are basically two types: fly ash and bottom ash. The use of fly ash in the composition of the composites cimentitious material makes it more sustainable. This study reports the characterization of two ashes coming from the burning of coal from two different capture processes to analyze the similarity between the ashes and their influence on concrete Portland cement. The concretes were produced by replacing part of the Portland cement by fly ash. The ashes were named CTP - I and CTP - II and were characterized in their physical, chemical, mineralogical and morphological properties. It was observed, through tests, that just one of fly ashes met the requirements of class C of NBR 12.653 (ABNT, 2014), the CTP - II, making possible the substitution of fly ash for cement. The other ash, CTP - I, presented a SO3 - concentration of approximately 12% and was initially used as fine material in the production of mortar, with the purpose to analyze the composite formed by leaching and solubilization tests to determine if there is danger in the production of these mortars. The experimental design was established in the production of a reference concrete and in the production of others concretes with the replacement of Portland cement by ash in the proportion 7,5% and 15% of Portland cement by fly ash, by volume, in three ratio water/binder different (0,4, 0,5 and 0,6). The properties of the concrete in the fresh and hardened state were analyzed by consistency tests, Fc, Ft, Ec, penetration of chlorides, among others, reference concrete and the concretes with ashes. The results of analyzes of concretes indicate that there is a technical viability of replacing Portland cement by fly ash, because in some concrete mixtures it was observed an increase of resistance to compression and decrease in the penetration of chlorides, besides other evidence. The results were analyzed statistically by analysis of variance (ANOVA). The mix with greater resistance to compression was the mix with CTP - I, w/b 0,4 and 7,5 of ash, whereas the one with lowest penetration of chlorides was the mix with CTP - II, w/b 0,4 and 15% ash.